pengaruh gaya kepemimpinan transformasional dan budaya kerja terhadap kedisiplinan kerja pegawai kelurahan caturtunggal depok sleman - hadi susilo (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT The purposes of this research are to know : (1) the effect of transformational leadership style on employee's work discipline at Caturtunggal district, Depok Sleman (2) the effect of work-culture on employee's work-discipline at Caturtunggal district, Depok Sleman (3) the effect of transformational leadership style and work- culture to employee's discipline at Caturtunggal district, Depok Sleman. This research is quantitative research which uses quantitative approach. Amount of this research are 45 employee and the sample are 38 people which is using sampling-technique with accidental method. The Data collecting technique is arranged with the questionnaires, while the data analysis technique used is multiple regression. The results of the research at a significant level of 5% showed that (1) transformational leadership style has no a significant effect on work- discipline with a significant value of 0.331 (p> 0.05). (2) There is a significant effect of work- culture to work- discipline with significant value equal to 0,002 (p <0.05). Both of transformational leadership and work- culture have a significant effect on employee's discipline. With a significant value of F of 0.000 (p <0.05). The contribution of transformational leadership style and work culture influence to work discipline of 57%. Keywood: Transformational Leadership, Work Culture and Work Discipline